Pengaruh Penambahan PEG 4000 terhadap Stabilitas Fisik Sediaan Pembersih Wajah dengan Basis Salep Larut dalam Air mengandung Nanoemulsi M/A Minyak Biji Anggur (Vitis vinifera) - Lany Diah Permatasari (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2019)
Abstract: UV radiation is one of the causes of photoaging. Grapeseed oil is one of natural components that contain antioxidant by inhibition mechanism of activation Mitogen-Activated Protein Kinase (MAPK) and Nuclear Faktor kB (NF-kB). The aim of this study was to know the effect of addition PEG 4000 on physical stability of facial cleanser with water soluble bases ointment containing o/w nanoemulsion of grapeseed oil. Facial cleanser with water soluble bases ointment was formulated using variation concentration of PEG 4000 (13%, 17% and 20%). Formulation were evaluated including physical appearance, pH, viscosity, spreadability, and stability testing. The optimum formula (F2) contained o/w nanoemulsion of grapeseed oil 33,5%, PEG 4000 17%, PEG 400 20%, stearic acid 13%, TEA 3% and Triethylhexanoin 13,5%, produce spreading ability 0,1828 ± 0,02 cm/g, pH 8,48 ± 0,01 and viscosity 460.00 ± 20.00 dPas. Based on the results of evaluation, F2 had a good facial cleansing ability. The formulation was physically stable. Keywords: grape seed oil, nanoemulsion, facial cleanser, water soluble ointment bases